Youth Christian Religious Education Strategy Based on Interactive Storytelling Through Social Media Platforms - Makoro, Aldi; Tangayo , Gilbert; Pangaribuan, Rosdinar; Nendissa, Julio Eleazer (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2026)
This study aims to develop a Christian Religious Education (CRE) strategy for youth relevant to the digital context through the use of interactive storytelling on social media platforms. The methods used were literature review and social media content analysis with a qualitative descriptive approach. The results showed that interactive storytelling which includes elements of participation, narrative choice, and direct feedback was proven to significantly increase youth's active engagement in the faith learning process. Indicators of this increase included the frequency of responses to posts, participation in follow-up discussions, and the emergence of personal and dialogic faith reflections. Furthermore, this strategy successfully built a sense of community ownership among youth, which has been a major challenge in conventional CRE, which tends to be one-way. The research findings identified that platforms such as Instagram, TikTok, and YouTube Shorts, with their interactive features (polls, questions, duets, stitches, and chain comments), are the most effective media for implementing this approach. The theoretical implications of this study emphasize the need for a paradigm shift in CRE from a static model of knowledge transmission to a dialogic, contextual, and creative model centered on youth's narrative experiences. Thus, interactive storytelling on social media is not just a tool, but a fundamental strategy capable of bridging the message of Christian faith with the everyday world of digital native youth. Keywords: youth CRE, interactive storytelling, social media, digital strategy.